S(h)ifting the cyberspace: searching for effectiveness and human rights balance in the realm of online enforcement schemes aimed at digital content infringing copyright, trademarks, privacy or reputation. - Garstka, Krzysztof (2016)
With the development of cyberspace, mankind’s ability to exchange tremendous amounts of information reached astonishing and praise-worthy levels. Unfortunately, such information also includes digital content infringing a variety of legitimate interests, such as copyright, trademarks, privacy, and reputation. Despite the increased regulatory activity of governments from all over the world, aimed at developing adequate legal frameworks governing the removal of access to such content, there are still significant concerns over the performance of this particular branch of online enforcement policy; concerns such as lack of effectiveness, or the impact of the endorsed solutions on the human rights framework.